The Development of Personal Injury Claim Mobile Applications using Odgen Table (Faculty of Computer and Mathematical Sciences, Universiti Teknologi MARA Perlis, 2019)
Personal injury claim can be found if any accident occurs such as road accident. After the accident occur the victim which is humankind can claim the compensation to himself regarding to injury in that accident. This claim involve law to determine the compensation amount to the victim. Unfortunately, in Malaysia multiplier-multiplicand approach still used by the court. This approach is outdated and unfair to victim as it’s not seen through the victim personal condition. So, the personal injury claim application which is it using Ogden table were implemented to calculate the compensation amount to victim. This Ogden table is special since it’s seen through in all aspect of victim personal condition. This application is build using Android Studio and Atom. This application has information about claimant, court and lawyer. It also can calculate the compensation amount more accurately to claimant. The target users of this application are claimant which is the victim, lawyer and court.